Comparison of the radiolabeled PSMA-inhibitor 111In-PSMA-617 and the radiolabeled GRP-R antagonist 111In-RM2 in primary prostate cancer samples - Schollhammer, Romain; De Clermont Gallerande, Henri; Yacoub, Mokrane; Quintyn Ranty, Marie-Laure; Barthe, Nicole; Vimont, Delphine; Hindié, Elif; Fernandez, Philippe; Morgat, Clément (EJNMMI research, 2019)
Purpose Prostate-specific membrane antigen (PSMA) and gastrin-releasing peptide receptor (GRP-R) are expressed in prostate cancer and can be targeted with radiolabeled inhibitors and antagonists. Their performances for the initial characterization of prostatic tumors have been barely evaluated but never compared. We aimed to gather comparative preclinical data of the role of PSMA and GRP-R targeting in prostate cancer. Procedures We retrospectively studied 20 frozen prostatectomy samples with various metastatic risks of the D’Amico classification. Tissue samples were investigated by tissular microimaging using the radiolabeled PSMA inhibitor 111 In-PSMA-617 and the radiolabeled GRP-R antagonist 111 In-RM2. Bindings of the two radiopharmaceuticals were compared to histology and clinico-biological data (Gleason score, PSA values, metastatic risks). Results Binding of 111 In-PSMA-617 was high whatever the metastatic risk ( p = 0.665), Gleason score ( p = 0.555), or PSA value ( p = 0.404) while 111 In-RM2 exhibited a significantly higher binding in the low metastatic risk group ( p = 0.046), in the low PSA value group ( p = 0.001), and in samples with Gleason 6 score ( p = 0.006). Conclusion PSMA and GRP-R based imaging might have complementary performances for the initial characterization of prostatic tumors. Prospective clinical studies comparing the two tracers in this setting are needed.